2019
DOI: 10.3390/mi10080498
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution of Time-Periodic Electroosmotic Flow through Cylindrical Microchannel with Non-Uniform Surface Potential

Abstract: Time-periodic electroosmotic flow (EOF) with heterogeneous surface charges on channel walls can potentially be used to mix species or reagent molecules in microfluidic devices. Although significant research efforts have been placed to understand different aspects of EOF, its role in the mixing process is still poorly understood, especially for non-homogeneous surface charge cases. In this work, dynamic aspects of EOF in a cylindrical capillary are analyzed for heterogeneous surface charges. Closed form analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…On the contrary, when is very large ( = 3000) , the near-wall liquid oscillates rapidly while the bulk fluid remains immobile; since there is not sufficient time for momentum to diffuse further into the remaining part of the fluid. These behaviors and trends are in agreement with the results of [35], e.g. with Fig.…”
Section: Potential and Velocity Fieldssupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, when is very large ( = 3000) , the near-wall liquid oscillates rapidly while the bulk fluid remains immobile; since there is not sufficient time for momentum to diffuse further into the remaining part of the fluid. These behaviors and trends are in agreement with the results of [35], e.g. with Fig.…”
Section: Potential and Velocity Fieldssupporting
confidence: 92%
“…It was shown that flow control has linear dependence on the value of the applied electric field. Khan and Dutta [35] analyzed EOF in a cylindrical microchannel for heterogeneous surface charges. They showed that several vortices are formed inside the channel with sinusoidal surface charge distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This transport method has been theoretically studied since many years ago in small channels with Newtonian fluids, as the early works carried out by Burgreen and Nakache [ 6 ] and Rice and Whitehead [ 7 ]. Since then and until now, the scientific community has continued studies on the electroosmotic flow behavior using Newtonian [ 8 , 9 , 10 , 11 , 12 ] and non-Newtonian fluids [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], addressing emerging issues regarding the rheology of the fluids and ionic concentrations, channel geometry, wall zeta potentials effects, boundary slip effects, among other topics, and their implications on the flow characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Microchannels are a fundamental part of microfluidic systems. A number of researches have been conducted to understand the mechanism of fluid flow and heat transfer characteristics in microchannels with circular [1,2,3], parallel plates [4,5,6], annular [7,8,9], rectangular [10,11,12,13,14,15] and trapezoidal [16,17,18] cross-sections. Compared with a circular duct, a better thermal efficiency can be found in an elliptical passage because the perimeter of an elliptical configuration is wider than the other for the same cross-sectional area [19].…”
Section: Introductionmentioning
confidence: 99%